Pengenalan Konsep Matematika di Masa Pandemi Covid–19 untuk Anak Usia Dini Menggunakan Alat Peraga - Anna Zuniasari; Fatrima Santri Syafri; Leta Santri Yusniarti; Reno Gustika Rahmat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to make efforts to introduce mathematical concepts during the Covid-19 pandemic for early childhood using teaching aids. This research is a type of library research or library research. Research result. Research result, there are several mathematical concepts that must be taught to early childhood, namely: (1) The concept of numbers (2) The concept of patterns and relationships (3) The concept of geometry and geometry (4) The concept of selecting and classifying (5) The concept of measurement (6) The concept data collection and display. In planting this mathematical concept, props are needed to make it easier for children to understand the mathematical concept. Props used to be taught by parents by connecting to the context of everyday life. This is in accordance with the introduction of mathematical concepts during the COVID-19 pandemic for early childhood using visual aids in understanding mathematical concepts during the COVID-19 transition. In conclusion, parents have an important role in the introduction of mathematical concepts in early childhood, the use of teaching aids in the surrounding environment is the easiest method in increasing understanding of simple mathematical concepts in early childhood. Keywords: Mathematical Concepts, COVID-19, Early Childhood, Teaching Aids